Effects of chronic exercise on growth factors in diabetic rats - Gomes, Ricardo José [UNESP]; Caetano, Flávio Henrique [UNESP]; De Mello, Maria Alice Rostom [UNESP]; Luciano, Eliete [UNESP] (My University, 2005)
The aim of the present study was to examine the influence of moderate physical training on the GH/IGF-1 growth axis in diabetic rats. Male Wistar rats were divided into 4 groups, sedentary control (SC), trained control (TC), sedentary diabetic (SD) and trained diabetic (TD). Diabetes was induced by Alloxan (35 mg/kg b.w.) The training program consisted by swimming 5 days/week, 1 h/day, supporting a load of 5 % body weight for 6 weeks. At the end of the training period, the rats were sacrificed and the blood was collected for determinations of serum glucose, insulin, GH, IGF-1 and IGFBP-3. Samples of liver and skeletal muscle were used to evaluate glycogen content. Tibia were collected for determination of total area. Diabetes decreased serum GH, IGF-1, IGFBP-3, total tibia area and liver glycogen stores in SD group (P<0.05). Physical training promoted increases in serum IGF-1 in both TC and TD groups and liver glycogen store, growth rate and tibia area in TD group when compared to sedentary SD (P<0.05). There was an inverse relationship between serum glucose and tibia area, growth rate, serum GH and serum IGF-1. Serum IGF-1 was positively correlated with tibia area and with growth rate. It was concluded that in diabetic rats, moderate physical training induces important metabolic and hormonal alterations that are associated with an improvement in glucose homeostasis and an increased activity of the GH/IGF-1 axis.
Keywords: Diabetes Mellitus; Growth Hormone; Insulin-like growth factor (IGF-1)